Temperature change affected groundwater quality in a confined marine aquifer during long-term heating and cooling. (1st May 2016) - Saito, Takeshi; Hamamoto, Shoichiro; Ueki, Takashi; Ohkubo, Satoshi; Moldrup, Per; Kawamoto, Ken; Komatsu, Toshiko
Abstract: Global warming and urbanization together with development of subsurface infrastructures (e.g. subways, shopping complexes, sewage systems, and Ground Source Heat Pump (GSHP) systems) will likely cause a rapid increase in the temperature of relatively shallow groundwater reservoirs (subsurface thermal pollution). However, potential effects of a subsurface temperature change on groundwater quality due to changed physical, chemical, and microbial processes have received little attention. We therefore investigated changes in 34 groundwater quality parameters during a 13-month enhanced-heating period, followed by 14 months of natural or enhanced cooling in a confined marine aquifer at around 17 m depth on the Saitama University campus, Japan. A full-scale GSHP test facility consisting of a 50 m deep U-tube for circulating the heat-carrying fluid and four monitoring wells at 1, 2, 5, and 10 m from the U-tube were installed, and groundwater quality was monitored every 1–2 weeks. Rapid changes in the groundwater level in the area, especially during the summer, prevented accurate analyses of temperature effects using a single-well time series. Instead, Dual-Well Analysis (DWA) was applied, comparing variations in subsurface temperature and groundwater chemical concentrations between the thermally-disturbed well and a non-affected reference well. Using the 1 m distant well (temperature increase up to 7 °C) and the 10 m distant well (non-temperature-affected), the DWA showed an approximately linear relationships for eight components (B, Si, Li, dissolved organic carbon (DOC), Mg 2+, NH4 +, Na +, and K + ) during the combined 27 months of heating and cooling, suggesting changes in concentration between 4% and 31% for a temperature change of 7 °C. Highlights: Effect of subsurface temperature change on groundwater quality was investigated. Concentration of several components increased linearly with increase in temperature. Boron concentration increased by 31% with increase in temperature of 7 °C. Elevated concentrations returned to original levels with decrease in temperature.